Marriage, adultery or polyandry? The Case of the Duchess of Medina Sidonia Dona Ana of Aragon at the Dawn of the 16th Century - Elipe, Jaime (Chronica Nova. Revista de Historia Moderna de la Universidad de Granada, 2021)
At the beginning of 16th century the situation in the kingdom of Seville was deeply turbulent. Ferdinand the Catholic decided to marry Dona Ana of Aragon to Guzman family, Dukes of Medina Sidonia in order to solve nobility conflicts and endow his granddaughter with a patrimony according to her royal blood. The marriage to the V Duke Don Juan Alonso took place in 1515. Due to his intellectual disability, the marriage was considered invalid at some uncertain moment. After that, Dona Ana married her brother-in-law, the V Duke’s brother. This resulted in a series of problems to find out the validity of this second marriage. The good relations with the imperial family facilitated the process that was undoubtedly irregular. T justified suspicion of illegitimacy that hung over the ducal family.